Famotidine inhibits glycogen synthase kinase-3β: An investigation by docking simulation and experimental validation. (August 2013) - Mohammad, Mohammad; Al-Masri, Ihab M.; Issa, Ala; Al-Ghussein, Mohamed A.S.; Fararjeh, Mohammad; Alkhatib, Hatim; Taha, Mutasem O.; Bustanji, Yasser
<x xml:space="preserve">Abstract</x> Famotidine was investigated as an inhibitor of glycogen synthase kinase-3β (GSK-3β) in an attempt to explain the molecular mechanism of its hypoglycemic side effects. The investigation included simulated docking experiments, in vitro enzyme inhibition assay, glycogen sparing studies using animal models and single dose oral glucose tolerance test (OGTT). Docking studies showed how famotidine is optimally fit within the binding pocket of GSK-3β via numerous attractive interactions with some specific amino acids. Experimentally, famotidine could inhibit GSK-3β (IC50 = 1.44 μM) and increased significantly liver glycogen spares in fasting animal models. Moreover, a single oral dose of famotidine was shown to decrease the glycemic response curve after 75 g OGTT